Improved systolic blood pressure (SBP)-lowering effect of stone fish-derived angiotensin-I converting enzyme (ACE)-inhibitory peptide entrapped in chitosan-coated alginate nanocomposites - Muhammad Auwal, Shehu; Muhammad Ghanisma, Siti Balqis; Saari, Nazamid (Elsevier Ltd, 2024)
Chitosan and alginate have been used as promising biodegradable polymers in the oral delivery of bioactive compounds. In the present study, the stone fish-derived ACE-inhibitory peptide, ALGPQFY was encapsulated through ionic gelation with alginate and polyelectrolyte complexation with sodium tripolyphosphate (TPP) cross-linked chitosan, to produce peptide loaded chitosan-coated alginate nanoparticles (PL-C-AL-NPs). The PL-C-AL-NPs were evaluated for physicochemical properties, morphology and thermal stability. The SBP-lowering effect due to the entrapped peptide was then studied on spontaneously hypertensive rats (SHRs). The results for physicochemical characterization revealed stable nanoparticles with small particle size and polydispersity index (pdi) of 212.60 nm and 0.327, and large values of entrapment efficiency (EE), peptide load (PL) and zeta potential of 74.48%, 16.67% and +46.80 mV, respectively. Transmission electron microscopy (TEM) displayed homogenously-dispersed vesicular nanoparticles while differential scanning calorimetry indicated a high thermal stability of the nanoparticles with the melting temperature of 143.39°C. The PL-C-AL-NPs exhibited a dose dependent SBP-lowering effect that was significantly higher (p < 0.05) compared to the free/unencapsulated peptide. This finding showed that, chitosan and alginate can be used in the design of nanocarriers to enhance the stability, bioavailability and antihypertensive efficacy of ALGPQFY which can be incorporated into functional foods and nutraceuticals for long-term hypertension management.